The role of Ca2+ signaling in Parkinson's disease - Sofia V. Zaichick; Kaitlyn M. McGrath; Gabriela Caraveo (The Company of Biologists, 2017)
Across all kingdoms in the tree of life, calcium (Ca2+) is an essential element used by cells to respond and adapt to constantly changing environments. In multicellular organisms, it plays fundamental roles during fertilization, development and adulthood. The inability of cells to regulate Ca2+ can lead to pathological conditions that ultimately culminate in cell death. One such pathological condition is manifested in Parkinson's disease, the second most common neurological disorder in humans, which is characterized by the aggregation of the protein, α-synuclein. This Review discusses current evidence that implicates Ca2+ in the pathogenesis of Parkinson's disease. Understanding the mechanisms by which Ca2+ signaling contributes to the progression of this disease will be crucial for the development of effective therapies to combat this devastating neurological condition.